Effects of maturation on knee biomechanics during cutting and landing in young female soccer players - Westbrook, A. E.; Taylor, J. B.; Nguyen, A.-D.; Paterno, M. V.; Ford, K. R. (PLOS ONE, 2020)
Young female soccer players are at high risk of anterior cruciate ligament injury due to the fast-paced nature of the sport and surplus of unplanned movements during play. Neuromuscular training programs that aim to reduce this injury by targeting the associated biomechanical movements are a potential solution. While previous studies have examined the lack of dynamic knee control during landing, there are few that outline the role that maturation can play during unanticipated cutting. Therefore, the purpose of this study was to determine if young female soccer players across multiple phases of maturation exhibited the before seen differences in knee control during a drop landing as well as an unanticipated cutting task. 139 female soccer players volunteered to participate in this study and were classified in three maturational groups based on percent adult stature: prepubertal (PRE), pubertal (PUB), and post-pubertal (POST). Each group performed a drop vertical jump (DVJ) and an unanticipated cutting task (CUT). Standard 3D motion capture techniques were used to determine peak knee flexion/abduction angles and moments during each task. Within tasks, POST exhibited significantly greater peak abduction angles and moments compared to PUB/PRE. While each maturational group exhibited greater peak knee abduction angles during the DVJ compared to the CUT, peak knee abduction moments during the CUT were greater compared to the DVJ. Participants within each maturational group exhibited greater knee flexion during the DVJ compared to the CUT, however there were no differences identified between groups. During both tasks, POST/PUB exhibited greater peak knee flexion moments compared to PRE, as well as POST compared to PUB. Overall, each group exhibited significantly greater peak knee flexion moments during the CUT compared to the DVJ. These observed differences indicate the need for neuromuscular training programs that target both jumping and cutting techniques to reduce ACL injuries.